Kamuflase dan Strategi Antipredasi Pada Kepiting Hantu Ocypode (Weber, 1795) di Pantai Congot, Kulonprogo, Yogyakarta - Pratiwi, Eka Mulia; Susilohadi, Susilohadi (Biospecies, 2019)
Antipredation is one type of adaptation done by prey animals in the face of predators, both avoid and fight. The antipredation strategy most often done by some animals is to trick predators, one of them by camouflage. In the camouflaged ghost crabs performed using background matching techniques, which alter their body colors and match them to the color of their environment by adjusting the concentration and dispersal of pigment in the chromatophore (Davies, 2013). In addition to camouflage, ghost crabs also make the hole as a hiding place from predators. With reference to camouflage and antipredation strategies on Ghost Crabs (Ocypode), It is necessary to conduct a study that examines the behavior of antipredation strategies that include camouflage and architecture of ghost crab burrows in Congot Beach, Kulonprogo, Yogyakarta. The method used in this research includes taking visible light portrait data using Ocypode and its environment to analyze the RGB value, then compare the RGB composition to the specimen and its environment with the Euclidean Distance index. In addition, data collection of burrow architecture using powder gypsum was sterilized with water and then allowed to dry and then the result of the mold is measured and analyzed. The results obtained, among others, the value of Euclidian Distance of 0.12 which indicates that the color on the carapaks are in accordance with the color of the environment. Furthermore, there were 29 cast of burrow architecture consisting of 20 I-shapes, 2 J-shapes, 2 L-shapes, 1 spiral 3 Y-shape, and 1 complex form.